Implementation of Human Resources Management Mosque Youth Bonding Program in Increasing the Prosperity Of The Amaliah Mosque, Sukarami Sub-District, Sukabangun Village 2 Palembang City - Tanti Indawati; Kusnadi Kusnadi; Candra Darmawan (CV. Ulil Albab Corp, 2023)
Quality mosque organizations need human resource development, what is meant by human resource development in this study is the implementation process carried out at the Amaliah Mosque, Sukarami District. The research entitled Implementation of Human Resource Management Program for Mosque Youth Associations in Improving the Prosperity of the Amaliah Mosque, Sukarami District, Sukabangun 2 Village, Palembang City. The research objectives were 1) to know the Implementation of Human Resource Management in the Mosque Youth Association Program in Increasing the Prosperity of the Amaliah Mosque, 2) to find out the inhibiting and supporting factors in the Human Resource Management Program for the Mosque Youth Association in Increasing the Prosperity of the Amaliah Mosque. This type of research is qualitative research. Data collection techniques include observation, interviews and documentation. The results of the study show that 1) The mosque youth level program is prepared to become children who have noble character, have an independent leadership spirit, memorize the 30 chapters of the Qur'an, have Islamic morals, implement HRM, integrate the tahfidz curriculum, dirosyah Islamiyyah and leadership as the soul of a teacher example. Teenagers memorize the Qur'an in 30 juz increments, equipped with a variety of religious material on the mulazamah system. 2) Supporting factors, namely directly from the taklim assembly, the availability of adequate funds and supervision so that simple activities carried out at the mosque appear to be successful because of good communication and cooperation between administrators and mosque youth. While the obstacles in the implementation, namely the lack of awareness of the people around the Amaliah mosque to participate in existing programs or activities on a regular basis, so that religious activities do not seem optimal, only from mosque youth who play an active role in the prosperity of the mosque.